FOREIGN AND DOMESTIC INVESTMENT IN INDONESIA: CROWDING IN OR CROWDING OUT? - Rizki Pratomo Sunarwibowo (Universitas Budi Luhur, 2018)
Investment is widely known as the main determinant in the process of country development, hence it supports economic growth. There are mainly two sources of investment, foreign and domestic. This paper contributes to the debate on how foreign direct investment (FDI) influence domestic investment, whether FDI crowds in or crowds out domestic investment. This paper also studies the role of government that affect the formation of investment in Indonesia. Using provincial level data from 2010 until 2015, this research finds that FDI does crowd in domestic investment. This concludes that FDI supports the formation of domestic investment, or in other words it has positive effect on domestic investment. Government performance also has positive effect on domestic investment.